PERANCANGAN SISTEM INFORMASI PENDATAAN WARGA NEGARA ASING (WNA) PADA KANTOR IMIGRASI KELAS 1 TPI JAMBI MENGGUNAKAN MOBILE WEB - Susanto, Darex; Setiawan, Tetra; Zulkifli, Heri (LP2M Universitas Nurdin Hamzah, 2023)
In 1992, based on Law Number 9 of 1992 concerning Immigration, Article 1 paragraph 15 states that immigration quarantine is a temporary shelter for foreigners who are subject to expulsion or deportation proceedings or other immigration measures. This is of course related to the immigration law, hence the term immigration quarantine as the beginning of Rundenim. . The Rudenim is led by a Head who has duties in the field of detention of foreigners, whose function is to take action, isolate and carry out the task of expulsion or deportation. In order for the data of foreign nationals to be processed properly, an application is needed that can support the work of the immigration office to record data properly and stored properly. That way it can make it easier to know the extent to which foreign nationals carry out their activities in Jambi Province. By using a mobile web device it will help staff who get the task of supervising and escorting them. The research was only conducted at the Jambi TPI Class 1 Immigration office. Applications are made using the PHP programming language and databases using MySql. With this design, it will make it easier for field officers to check and find out the whereabouts of foreign nationals in Jambi Province.